Investigation of Negative Effects of Zoning Peace on Urban Conservation from the Perspective of Istanbul Historical Peninsula - (:unkn) unknown (KARE PUBL, 2021)
The Zoning Peace arrangement, which can be called the last version of zoning amnesties, was implemented in 2018 and was discussed in many ways. The building, which collapsed in Kartal on 06.02.2019 and appeared to be a Zoning Peace application, and the 5.8 magnitude earthquake in Silivri on 26.09.2019 made the status of the building stock in Istanbul controversial. The region, known as the Historical Peninsula and overlapping the borders of Fatih district, is critical due to the historical and architectural value of the building stock and its risk status. The fact that a large part of Fatih is covered by the law has enabled the illegal construction elements in the district to be legalized. This created an alarming situation in terms of the life safety of the residents and the continuity of the historical texture and cultural heritage of the district. This current and critical situation is the starting point of the article. The revealing of the contradictions between Zoning Peace and urban conservation and the preservation of the cultural heritage of the Historic Peninsula were highlighted as the aim of the article, and in this context, the negative effects of the law were determined. In order to emphasize the importance of the focus of the article, extensive literature consisting of the works of Ilhan Tekeli, who has many studies on the relationship between the concepts of planning and conservation, has been examined. Tekeli's own expertise, planning and urban conservation comments, which he says gives great importance, have been compiled. In addition, the literature on the principles and practices of urban conservation has been examined and the theoretical infrastructure of the article has been strengthened. The current situation and risks of the Historic Peninsula, which were noticed throughout the article, were made visible by photographing the problematic building stock in many points of the district. Based on this, various determinations were made and suggestions were presented. With this study, it was tried to draw attention to the problems that Zoning Peace may cause in historical city centers and the Historical Peninsula, and to create an awareness.
Keywords: Zoning amnesty; zoning peace; urban conservation; cultural heritage; historical peninsula